Effects of Process Parameters on the Surface Roughness of Stainless Steel 316L Parts Produced by Selective Laser Melting - Derahman, Nur Aqilah; Sayuti, Mohd; Yusof, Farazila; Dambatta, Yusuf Suleiman; Amran, Nor Amirah Mohd; Badiuzaman, Wan Nur Izzati Wan (ASTM International, 2018)
Selective Laser Melting (SLM) is an additive manufacturing method that is used to fabricate different types of complex components using a layer-by-layer approach. The parts are produced directly from three-dimensional computer-aided design data by melting the powdered material layer-by-layer with the aid of laser power. In this work, an experimental investigation of the process parameters of the SLM method using stainless steel 316L powder was conducted. The influence of laser power, scanning speed, and hatching distance on the surface roughness of the specimens was investigated. The design of experiment was conducted using Taguchi’s L16 orthogonal array. Furthermore, statistical analysis using signal-to-noise (S/N) response and analysis of variance (ANOVA) was used to obtain the optimal parameter combinations of the SLM process. From the experimental results, it was found that laser power has the greatest effect on the surface roughness relative to scanning speed and hatching distance. Moreover, using regression analysis, the predicted values of surface roughness and signal-to-noise ratios were obtained. The predicted values were then compared with the experimental values. Lastly, shot peening technique was used to improve the surface roughness of the manufactured components. The results show that the shot peening process offers about 33.28 % reduction in the surface roughness of the manufactured parts.